The Role of Environmental Ethics and Training in Enhancing Performance and Competitive Advantage - Al Basheer, Shahid; Javad, Sayedy (Analisis Data Innovation, 2024)
Purpose – This study emphasizes the importance of environmental ethics, education and training in the progress of environmental performance, competitive advantage and the sustainability of organizations. It seeks to evaluate both the direct and indirect impacts of these factors on companies’ long-term strategic positioning.Design/methodology/approach – This research utilizes a quantitative method and is based on administering a survey comprising data on 424 middle-level managers from various sectors in the UAE. SEM analysis on environmental ethics, education, training, performance, and competitive advantage.Findings – The study sends a message that environmental ethics have a positive influence on environmental performance, education and internal operation training, which will improve competitive advantage. Moreover, environmental training on firm performance and competitive positioning is highly significant. Other effects are indirect where performance and education function as mediators.Originality/value – This research empirically investigates how environmental ethics, education and training could help firms to attain sustainability and competitive advantage. These results underscore the strategic significance of embracing environmental initiatives within corporate policies.Research Implications – The findings highlight the critical need for companies to invest in environmentally ethical operational practices, capabilities, and education to foster sustainability. Further research may investigate the sector-specific effects, and further explore the structural relationships over the longer term, via longitudinal data.